Imvuselelo: Embers of liberation in South Africa post-1994 - Vellem, Vuyani S. (HTS teologiese studies, 2016)
The unprecedented cultural consciousness after decades of black cultural suppression in the South African public life since the 1990s summons us to the need to harness African ecclesiopolitical symbols in public life. This task is executed at a time when the notions of inter alia, spirituality and Imvuselelo are at the heart of the combustion chambers of our public and political life. Imvuselelo is a thermometer of decolonialist rebellion – the militant spirituality linked with Tiyo Soga – and is a self-combustion escape route in instances of black African epistemicide and violence. The heuristic device of iziko (fireplace) is employed to illuminate and locate the reestablishment and anamnestic praxis of protological life-giving foundations of spirituality in the African universe in our interpretation of Imvuselelo. The notion of imvuselelo is illuminated through iziko to debunk the incompatibilities, disharmonies, incongruences and conflagrations of virtual spirituality in its capture and domestication of the resources of the downtrodden.